Propriedades fotoquímicas do complexo fac-[Re(CO)3(dcbH2)(trans-stpy)+ - Faustino, Leandro Augusto (2018)
The present work describes the spectroscopic, photophysical, photochemical and photoelectrochemical properties of the fac-[Re(CO)3(dcbH2)(trans-stpy)]+ complex (dcbH2 = 4,4'-dicarboxylic acid-2,2'-bipyridine, trans-stpy = trans-4-styrylpyridine). The compound was characterized by proton nuclear magnetic resonance spectroscopy (1H NMR) and infrared spectroscopy to prove its structure and purity. Its absorption spectrum in the UV-Vis region shows a broad absorption band from 390 to 500 nm, ascribed to the metal to the ligand dcbH2 charge transfer transition (MLCT). In the region from 330 to 380 nm, the absorption occurs through trans-stpy internal transitions. These interpretations were corroborated by theoretical simulations. Spectral variations are observed under irradiation in 405 nm and 365 nm and are attributed to the trans-cis photoinduced isomerization of the coordinated stpy ligand. The isomerization quantum yields () were determined by 1H NMR and are wavelength dependent. While for irradiation at 405 nm,  = 0.010, for 365 nm,  = 0.81. The observed photochemical behavior was rationalized based on the relative energy of the lower energy excited states. Both isomers exhibit luminescence at 298 K when excited in the MLCT absorption region , with similar quantum yields em = 0.001. The radiative decay is attributed to the 3MLCT excited state. The two isomers were anchored on the surfaces of TiO2 and Al2O3 thin films and the photoelectrochemical properties of the sensitized films were investigated. In TiO2, both isomers are capable of generating photocurrent when excited at 405 nm and 365 nm and the electron injection quenches the trans-cis photoisomerization on the surface of the metal oxide. The photoisomerization does also not occur on the surface of Al2O3 in which electron injection is not favored due to the more negative potential of the Al2O3 conduction band. From the data obtained it was possible to elucidate the participation of the excited states as a function of the irradiation wavelength and to propose the possible ways to deactivation of these excited states.